Actuation fatigue life prediction of shape memory alloys under the constant-stress loading condition. (15th January 2015) - Calhoun, C.; Wheeler, R.; Baxevanis, T.; Lagoudas, D.C.
Abstract : The efficiency of the critical plane model of Smith, Watson, and Topper is demonstrated for the actuation lifetime prediction of shape memory alloys undergoing thermal cycling while under constant tensile stress. The model can be in principle extended to more complex actuation loading paths and predict the critical plane for failure in structural components. It is moreover important to note the correlation of the model to the actuation energy density for the data used for its experimental verification.